Factor influencing the tourism Development in kota bharu, kelantan - Nurul Izzati Syuhada Abd Basir; Nurul Nabila Azman; Nurul Nabila Jamaluddin; Nurul Nadia Izzah Shafie (2023)
This research observes the relationship of tourism development in Kota Bharu, Kelantan in 3 aspects which is food image, destination image and Islamic values. The objectives of this research is firstly to investigate the relationship of food image between tourism development in Kota Bharu, Kelantan. Secondly, this is to identify the relationship between destination image between tourism development in Kota Bharu, Kelantan and thirdly is to determine the relationship of Islamic values between tourism development in Kota Bharu, Kelantan . 384 local tourists from Kelantan and people who visit Kelantan will be target to be the respondent and answered the survey which is questionnaire by face to face. The Statistical Package for Social Science(SPSS) will use in order to evaluate the data collection. The function of SPSS is to statethe whole statistical analysis process which is to plan, to collect the data, report for the best decision making and also performance. This study will further strengthened claim of previous research on how food image, destination image and Islamic values influence the current dependent variable. Lastly, this study significantly contributes to development and the industry in Kelantan based on food image, destination image and Islamic values as the contributing factors. Keywords: food image, destination image and Islamic values, tourism development